Analysis of the Application of the Six Sigma Method in Quality Control of Floating Equipment Products (Case Study: Manufacturing Industry) - Pratiwi, Meilisa Ayu; Utomo, Dutho Suh (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
The company engaged in manufacturing with a focus on producing oilfield equipment used for drilling exploration wells, especially the cementing process. One of the tools produced is floating equipment. To identify and maintain the quality of floating equipment products, the Six Sigma and Kaizen 5W1H methods are used. At the define stage, it is determined that the problems that occurred during the 2023 period with a total production of 923 units and 90 units of defects, there are 5 types of defects in the form of, non-conforming cement test results, unmatch components, damaged materials, non-conforming sizes, and non-conforming thread profiles, based on CTQ and Pareto diagrams, the main priority for improvement is the type of defects in non-conforming cement test results, unmatch components, and damaged materials. At the measure stage, the DPMO (defect per million opportunity) calculation is 19,501.625 with a sigma level of 3.5642, this value shows that improvements are still needed in the production process of floating equipment products. The proposed improvements focus on training production operators and overcoming human error, maintenance and inspection of machines and other tooling, increasing inspection and supervision and paying attention to the storage and treatment of the materials used.